Problem-based Learning: A Methodological Alternative for strengthing the Subject of Law in the Classroom - Tibocha-Juliao, Judith (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Education must contribute to the construction of a society that embraces democracy as a way of life, which also requires the constitution of subjects of law who contribute with their actions to generate peace and counteract inequity. For this, it is necessary to orient the pedagogical processes through methods that allow students to strengthen their skills and capacities to relate to others and to acquire the necessary knowledge, internalize it and put it into practice. The present article analyzes the methodology of Problem-Based Learning as a strategy that allows strengthening the subject of law in the classroom in secondary students, responding to training in and for human rights that makes possible the development of a society in peace and better for all.